THE IMPACT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY OF LARGE FIRMS IN SERBIA - Milošev, Ivana (Poslovna ekonomija, 2022)
THE IMPACT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY OF LARGE FIRMS IN SERBIA ABSTRACT: Short term firms decisions about working capital influence on firms value and profitability. This study aims to find new empirical evidence of the influence of managing workig capital on profitability, measured by ROA, with application to 367 large non-financial firms in Serbia during four-year period (2016-2019) using panel-corrected standard error model. The results show that after controlling for characteristics of the firm and macroeconomic conditions working capital management has statistically significant and non linear influence to firm profitability. This suggest existence of an optimal level of net working capital of analysed firms, till optimal level working capital has positive and above optimal level workig capital has negative effect to firm profitability. KEY WORDS: working capital, profitability, large firms in Serbia